ANALISIS PERAN HUBUNGAN MASYARAKAT DI SMK PAWIYATAN SURABAYA - Rahmayanti, Amelia; Puspasari, Durinda (Jurnal Prospek: Pendidikan Ilmu Sosial dan Ekonomi, 2023)
The aim of this research is to analyze the role of community relations at Pawiyatan Vocational High School, Surabaya. This research is descriptive research with a qualitative approach. The data collection technique is interviews and data validity using source triangulation. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The results of the research show that the role of public relations at Pawiyatan Vocational High School Surabaya focuses more on problems that occur internally. The role of public relations at Pawiyatan Vocational High School Surabaya includes the role of school public relations in student PKL program activities which contributes from seeking cooperation from company agencies to the final stage of preparing student proposals; the role of school public relations in collaborating with DU/DI to discuss the issue of synchronizing the curriculum and the teaching industry; the role of school public relations in scholarship management activities, public relations seeks organizational sources that are able to provide scholarship funds so that students can enjoy decent educational facilities with reduced financial burdens; 4) public relations communications when carrying out school programs are able to establish good relationships with internal and external communities.